LECSICO-SEMANTICHNA STRUCTURE OF CONTSEPTIV ’DIVCHYNA’, ’JINKA’, ’BABA’ / ’DZIEWCZYNA’, ’KOBIETA’, ’BABA’ IN UKRAINIAN AND POLISH LANGUAGES: COMPARATIVE ASPECT - Lazarovich, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article deals with the comparative concepts „girl“, „woman“, „grandmother“ in the Ukrainian and Polish lanquaqes.